Central Peripheries Nationhood in Central Asia - Laruelle, Marlene (FRINGE, 2021)
Central Peripheries explores post-Soviet Central Asia through the prism of nation-building. Although relative latecomers on the international scene, the Central Asian states see themselves as globalized, and yet in spite of - or perhaps precisely because of - this, they hold a very classical vision of the nation-state, rejecting the abolition of boundaries and the theory of the 'death of the nation'. Their unabashed celebration of very classical nationhoods built on post-modern premises challenges the Western view of nationalism as a dying ideology that ought to have been transcended by post-national cosmopolitanism. Marlene Laruelle looks at how states in the region have been navigating the construction of a nation in a post-imperial context where Russia remains the dominant power and cultural reference. She takes into consideration the ways in which the Soviet past has influenced the construction of national storylines, as well as the diversity of each state's narratives and use of symbolic politics. Exploring state discourses, academic narratives and different forms of popular nationalist storytelling allows Laruelle to depict the complex construction of the national pantheon in the three decades since independence. The second half of the book focuses on Kazakhstan as the most hybrid national construction and a unique case study of nationhood in Eurasia. Based on the principle that only multidisciplinarity can help us to untangle the puzzle of nationhood, Central Peripheries uses mixed methods, combining political science, intellectual history, sociology and cultural anthropology. It is inspired by two decades of fieldwork in the region and a deep knowledge of the region's academia and political environment.Praise for Central Peripheries 'Marlene Laruelle paves the way to the more focused and necessary outlook on Central Asia, a region that is not a periphery but a central space for emerging conceptual debates and complexities. Above all, the book is a product of Laruelle's trademark excellence in balancing empirical depth with vigorous theoretical advancements.' -Diana T. Kudaibergenova, University of Cambridge 'Using the concept of hybridity, Laruelle explores the multitude of historical, political and geopolitical factors that predetermine different ways of looking at nations and various configurations of nation-building in post-Soviet Central Asia. Those manifold contexts present a general picture of the transformation that the former southern periphery of the USSR has been going through in the past decades.' - Sergey Abashin, European University at St Petersburg